Learning Multi-Level Skill Hierarchies with Graphwave - Bele, Simon; Žabkar, Jure (Proceedings of the10th Student Computing Research Symposium (SCORES’24), 2024)
We introduce a novel framework for learning multi-level skill hi-erarchies in reinforcement learning environments by leveraging structural similarities in state-space graphs. To obtain structural embeddings, we use the Graphwave algorithm, which places struc-turally similar states in close proximity in the latent space. In the latent space, we perform hierarchical clustering of states while respecting the topology of the state-space graph. At different levels of the hierarchy we learn the options that represent the skills; a skill at each level of the hierarchy is defined using the skills from the level below. We compare our approach with the state-of-the-art method across several environments. Our results show that structural embeddings can speed up option learning significantly in certain domains.